Murmur clinic: validation of a new model for detecting heart valve disease. Issue 1 (26th July 2018) - Draper, Jane; Subbiah, Sheila; Bailey, Rikki; Chambers, John B
Abstract : Objectives: We aimed to determine if auscultation or a point-of-care scan could reduce the need for standard echocardiography (transthoracic echocardiogram (TTE)) in community patients with asymptomatic murmurs. Methods: Requests from general practitioners were directed to a new murmur clinic. Auscultation and a point-of-care scan were performed by a cardiologist between 1 October 2013 and 31 December 2014 and by a scientist between 21 July 2015 and 9 May 2017. Results: In the first phase (cardiologist), there were 75 patients, mean age 54 (56 women), and in the second phase there were 100 patients, mean age 60 (76 women). In the total population of 175, abnormalities were shown on TTE in 52 (30%), on point-of-care scan in 52 (30%) and predicted on auscultation in 45 (26%) (p=0.125; 95% CI −0.02 to 0.29). The sensitivity of auscultation was not significantly different for the cardiologist (91%) as for the scientist (83%) (p=0.18; 95% CI −0.22 to 0.175) and the specificity was 100% for both. Accuracy was 97% for the cardiologist and 95% for the scientist. For the point-of-care scan, the sensitivity, specificity, positive and negative predictive values and accuracy were 100% for both cardiologist and scientist. Conclusion: Most patients in a specialist murmur clinic had normal auscultation and point-of-care scans and no additional valve disease was detected by standard echocardiography. This suggests that a murmur clinic is a valid model for reducing demand on hospital echocardiography services.